HESPER web - development and reliability evaluation of a web-based version of the humanitarian emergency settings perceived needs scale - K. Hugelius; M. Semrau; M. Holmefur (BMC, 2020)
Abstract Background The Humanitarian Emergency Settings Perceived Needs Scale (HESPER) assesses a wide range of physical, psychological and social perceived needs across 26 questions, and can be used in humanitarian emergencies and disasters for needs assessment or research studies. The original HESPER collects data through individual interviews. Today, a large number of people have access to the internet, including in humanitarian emergencies and disasters. Therefore, this paper aimed to report the development, reliability evaluation and feasibility evaluation of the HESPER Web. Methods First, the original HESPER was developed into a web based survey. Thereafter, alternate forms reliability between the HESPER and HESPER Web, and test-retest reliability for the HESPER Web, was evaluated using a study sample of 85 asylum seekers in Sweden in total. Results The alternate forms reliability evaluation showed that the HESPER Web was a reliable instrument to assess perceived needs. Intraclass correlation coefficient (ICC) for total number of serious needs was 0.96 (CI 0.93-09.98, p < 0.001). Cohen's κ was used to analyse the alternate forms reliability between the HESPER and HESPER Web item per item; the correspondence between HESPER and HESPER Web varied between 0.54 and 1.0 for the 26 questions. There was a strong nominal association in first priority need between the HESPER and HESPER Web (Cramer's V 0.845, p < 0.001). In the test-retest reliability evaluation of HESPER Web, ICC was 0.98 (CI 0.97-0.99, p < 0.001), and Cohen's κ varied between 0.53 and 1.0. There was a strong nominal association in first priority need between test and re-test (Cramer's V 0.93, p < 0.001). The HESPER Web was experienced as easy and safe to use and was found less time consuming than the original HESPER interview, according to the study participants. Conclusion The HESPER Web is a reliable and usable instrument to assess perceived needs. It can reduce a number of practical challenges both for needs assessment in disasters or humanitarian emergencies as well as in research.